Natural Variation in Clinical Isolates of Candida albicans Modulates Neutrophil Responses - Madhu Shankar (American Society for Microbiology, 2020)
ABSTRACT Neutropenia predisposes patients to life-threatening infection with Candida albicans, a commensal and opportunistic fungal pathogen. How phenotypic variation in C. albicans isolates dictates neutrophil responses is poorly understood. By using a panel of clinical C. albicans strains, here we report that the prototype strain SC5314 induces the most potent accumulation of reactive oxygen species (ROS) and neutrophil extracellular traps (NETs) by human neutrophils of all tested isolates. ROS and NET accumulation positively correlated with the degree of hyphal formation by the isolates, the hypha being the fungal morphotype that promotes pathogenesis. However, there was no correlation of ROS and NET accumulation with fungal killing by neutrophils. Fungal killing was also not correlated with phagocytosis levels or oxidative stress susceptibility of the isolates. The bloodstream isolate P94015 cannot make hyphae and was previously shown to be hyperfit in the murine gut commensalism model. Our results show that P94015 displays poor phagocytosis by neutrophils, the least ROS and NET accumulation of all tested isolates, and resistance to neutrophil-mediated killing. Our data suggest that reduced susceptibility to neutrophils is likely to be independent from a previously described genetic mutation in P94015 that promotes commensalism. Reduced clearance by neutrophils could benefit commensal fitness of C. albicans and could also have promoted the virulence of P94015 in the human patient in the absence of hyphal morphogenesis. Collectively, our study provides new insights into neutrophil interactions with C. albicans and suggests that studying diverse isolates informs knowledge of the relevant aspects of this key immune interaction. IMPORTANCE Neutrophils are the key immune cell type for host defenses against infections with Candida albicans. C. albicans strains isolated from patients display large phenotypic diversity, but how this diversity impacts host-pathogen interactions with neutrophils is incompletely defined. Here, we show that important neutrophil responses, such as accumulation of reactive oxygen species and neutrophil extracellular traps, as well as the levels of phagocytosis and killing of the pathogen, differ when comparing diverse C. albicans isolates. A bloodstream patient isolate previously described as more suited to commensalism than pathogenesis in animal models is relatively “silent” to neutrophils and resistant to killing. Our findings illuminate the relationships between fungal morphogenesis, neutrophil responses, and C. albicans survival. Our findings suggest that host phenotypes of a commensally adapted strain could be driven by resistance to immune clearance and indicate that we should extend our studies beyond the “prototype” strain SC5314 for deeper understanding of Candida-neutrophil interactions.